Remapping sovereignty decolonization and self-determination in North American indigenous political thought - Temin, David Myer (The University of Chicago Press, 2023)
"An original account of the stakes of sovereignty for recovering anticolonial pasts and fashioning anticolonial futures. Despite their signal contributions to present-day anticolonial struggles from #NODAPL to Idle No More, Indigenous societies around the globe are recurrently neglected in histories and theories of decolonization. What results from this disregard is not only skewed history, but also diminished political horizons for those (Indigenous and non-Indigenous) striving to transform an unequal world profoundly shaped by colonialism. Bridging political theory and Indigenous Studies, political theorist David Temin shows how key 20th-century Indigenous intellectual-activists in lands today claimed by Canada and the United States fundamentally recast the philosophical substance and normative goals of decolonization. Through history, textual interpretation, and conceptual analysis, his book recasts a vision of anticolonial thought and agency that circles around a politics of self-determination disentangled from sovereignty as institution and ideal-one committed to the relational flourishing of human and other-than-human beings against colonial domination"--Provided by publisher.